Preliminary report: April 2009 - August 2010 National Inflammatory Arthritis Registry (NIAR) - Rosman, Azmillah; Lau, Ing Soo; Mohd Zain, Mollyza; Mohd Yusoof, Habiba@Habibah; Mohamed Ismail, Asmahan; Chong, Hwee Cheng; Kuan, Woon Pang; Arumugan, Ramani; Shereen, Ch'ng Suyin; Abdullah, Hilmi; Ong, Yew Chong; Shukor, Ramlah; et al. (Clinical Research Centre, Hospital Selayang, 2010)
Rheumatoid Arthritis (RA) is the most common form of infl ammatory arthritis. It is estimated to affect about 1% of the population. Of unknown aetiology, it typically affects many joints, causing acute inflammation, in most cases leading to joint erosions and joint damage (1). The NIAR, initiated in 2008, was set up with the aim of obtaining information about patients with Rheumatoid Arthritis. Information about patients with the other inflammatory arthritides will be collected in the future.